Perfluoroalkyl-Functionalized Covalent Organic Frameworks with Superhydrophobicity for Anhydrous Proton Conduction - Wu, Xiaowei; Hong, You-lee; Xu, Bingqing; Nishiyama, Yusuke; Jiang, Wei; Zhu, Junwu; Zhang, Gen; Kitagawa, Susumu; Horike, Satoshi (Journal of the American Chemical Society, 2020)
The development of anhydrous proton-conducting materials is critical for the fabrication of high-temperature (>100 °C) polymer electrolyte membrane fuel cells (HT-PEMFCs) and remains a significant challenge. Covalent organic frameworks (COFs) are an emerging class of porous crystalline materials with tailor-made nanochannels and hold great potential for ion and molecule transport, but their poor chemical stability poses great challenges in this respect. In this contribution, we present a bottom-up self-assembly strategy to construct perfluoroalkyl-functionalized hydrazone-linked 2D COFs and systematically investigate the effect of different lengths of fluorine chains on their acid stability and proton conductivity. Compared with their nonfluorous parent COFs, fluorinated COFs possess structural ultrastability toward strong acids as a result of enhanced hydrophobicity (water contact angle of 144°). Furthermore, the superhydrophobic 1D nanochannels can serve as robust hosts to accommodate large amounts of phosphonic acid for fast and long-term proton conduction under anhydrous conditions and a wide temperature range. The anhydrous proton conductivity of fluorinated COFs is 4.2 × 10–2 S cm–1 at 140 °C after H3PO4 doping, which is 4 orders of magnitude higher than their nonfluorous counterparts and among the highest values of doped porous organic frameworks so far. Solid-state NMR studies revealed that H3PO4 forms hydrogen-boding networks with the frameworks and perfluoroalkyl chains of COFs, and most of the H3PO4 molecules are highly dynamic and mobile while the frameworks are rigid, which affords rapid proton transport. This work paves the way for the realization of the target properties of COFs through predesign and functionalization of the pore surface and highlights the great potential of COF nanochannels as a rigid platform for fast ion transportation.